All-optical NOT Logic Based on Asymmetric SOA-Assisted Mach-Zehnder Interferometer - Xiaohua Ye (Institute of Advanced Engineering and Science, 2012)
A novel scheme for all-optical NOT logic which exploits the cross-phase modulation (XPM) effect in an asymmetric SOA-assisted Mach-Zehnder Interferometer (SOA-MZI) has been proposed for the first time. Only two input beams are employed to achieve NOT operation in this new design. The scheme is validated and the system performance is optimized with various parameters through numerical simulations. This compact logic gate is helpful for future all-optical computing and networks.